The 36th Annual Meeting of the Middle East Studies Association of North America (American Journal of Islam and Society, 2003)
The 36th annual meeting of the Middle East Studies Association of NorthAmerica (MESA), was held at the Wardman Park Hotel, Washington, DC,November 23-26, 2002. This conference, possibly the largest gathering ofscholars and students of the Middle East, took place in an atmosphere saturatedby 9/11 and Washington’s plans for an all-out war against Iraq, aswell as considerable right-wing and pro-Zionist pressure applied by suchmembers of the epistemic community of scholars, journalists, and policyanalysts as Daniel Pipes (the Middle East Forum) and Martin Kramer, aone-time director and currently a senior research fellow at Tel AvivUniversity’s Moshe Dayan Center for Middle Eastern and African Studies.Both are behind Campus Watch (http://www.campus-watch.org), whichmonitors academic discourse that opposes American foreign policy towardthe Muslim world and its one-sided support for Israel, and which maintainson its website a list of “un-American” academicians and apologists for“militant Islam” and rogue regimes.November 23, the first day, was reserved for the business meetings ofall groups having an institutional affiliation with MESA. The panels, presentedas parallel sessions, began on Sunday at 8:30 a.m. Also featured wasa presidential address by the outgoing president, a plenary session, a bookexhibition, an art gallery, and a film fest. MESA organizers reported that1,900 people attended the 156-panel event, along with 80 exhibitions.The first session featured panels on popular culture and identity in theMaghreb, women and development, issues in contemporary Iran, intellectualsand ideas in the making of the Turkish Republic, history of the Ottomanborderlands, legitimation of authority in early period of Islam, comparativeperceptions of the “other” in Israeli and Palestinian textbooks, comparativeanalysis of political Islam, religious conversion and identity, and the Arabicqasidah. There was also a roundtable discussion on water issues and a thematicconversation on 9/11 and the Muslim public sphere. In the following ...